Tumour Necrosis Factor-A Is the Signal Induced by Mating to Shutdown a 2-Methoxyestradiol Nongenomic Action Necessary to Accelerate Oviductal Egg Transport in the Rat - Cardenas-Sankan, G; Orihuela-Diaz, P; Orostica, M (2013)
Mating shut down a 2-methoxyestradiol (2ME) nongenomic action necessary to accelerate egg transport in the rat oviduct. Herein, we investigated whether tumour necrosis factor-a (TNF-a) participates in this mating effect. In unmated and mated rats, we determined the concentration of TNF-a in the oviductal fluid and the level of the mRNA for Tnf-a (Tnf ) and their receptors Tnfrsf1a and Tnfrsf1b in the oviduct tissues. The distribution of the TNFRSF1A and TNFRSF1B proteins in the oviduct of unmated and mated was also assessed. Finally, we examined whether 2ME accelerates oviductal egg transport in unmated rats that were previously treated with a rat recombinant TNF-a alone or concomitant with a selective inhibitor of the NF-kB activity. Mating increased TNF-a in the oviductal fluid, but Tnf transcript was not detected in the oviduct. The mRNA for TNF-a receptors as well as their distribution was not affected by mating, although they were mainly localized in the endosalpinx. Administration of TNF-a into the oviduct of unmated rats prevented the effect of 2ME on egg transport. However, the NF-kB activity inhibitor did not revert this effect of TNF-a. These results indicate that mating increased TNF-a in the oviductal fluid, although this not associated with changes in the expression and localization of TNF-a receptors in the oviductal cells. Furthermore, TNF-a mimicked the effect of mating on the 2ME-induced egg transport acceleration, independently of the activation of NF-kB in the oviduct.We concluded that TNF-a is the signal induced by mating to shut down a 2ME nongenomic action in the rat oviduct. © 2013 Society for Reproduction and Fertility.